Surface effects on vortex dynamics in thin type-II superconducting stripes with random pinning - Reis, J. D.; Venegas, Pablo Antonio [UNESP]; Mello, Denise Fernandes de [UNESP]; Cabrera, G. G. (Elsevier B.V., 2004)
We analyze the dynamics of a driven vortex lattice moving in a thin Superconducting stripe. The two dimensional stripe is assumed to be finite in the longitudinal direction, where we take into account the Surface effects, and infinite in the transversal direction. The numerical simulations are performed using the Langevin dynamics, including the vortex-vortex interaction, interaction of vortices with the surface current, vortex images, transport current and randomly distributed pinning centers. We show results for the differential resistivity and the vortex trajectories as a function of the external force. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: superconductivity; vortex dynamics; size effects